Method for manufacturing adhesive, adhesive body, and pressure-bonded body
By bonding with fluoroelastomer glue in a specific state of carbon dioxide, the problem of bonding of fluorine-based materials is solved, and efficient and low-energy colloid formation is achieved, while maintaining the shape and physical properties of the substrate.
Patent Information
- Application Number
- JP2021567296
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2020-12-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-12-15
AI Technical Summary
It is difficult for the prior art to effectively bond substrates using fluorine-based materials, and the traditional thermal fusion bonding method is harmful to the shape and physical properties of the substrate, and it consumes a high energy consumption.
The bonding is carried out in the liquid state, gas-liquid mixed state of carbon dioxide or near liquid state, and the substrates are fixed by pressure to form colloids with desired shape.
The efficient bonding of fluorine-based materials is achieved, ensuring the chemical resistance and low external heat input of the colloid, and the energy consumption is reduced, and the shape and physical properties of the substrate are kept intact.
Smart Images

Figure 0007649512000005 
Figure 0007649512000006 
Figure 0007649512000007
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to a method for producing an adhesive, a bonded body, or a pressure-bonded body. [Background technology]
[0002] Substrates such as nonwoven fabrics, woven fabrics, fibers, porous membranes, and films may be used alone or in combination with a plurality of the same substrates or with other substrates.
[0003] When substrates are laminated in this manner, a method is usually used in which the substrates are bonded together using an adhesive by reacting components contained in the adhesive or volatilizing the solvent, or the substrates are bonded together by melting the adhesive layer or the substrate itself and heat fusing them.
[0004] The method of bonding substrates together using the adhesive has the advantage that the substrates can be bonded together easily, but the obtained bonded body may have problems with the heat resistance of the adhesive part, or foreign matter may be mixed in or contamination may occur at the adhesive part, leaving room for improvement in this regard.
[0005] In addition, the method of bonding substrates together by heat fusion has the advantage that an adhesive with high adhesive strength can be obtained, but the freedom of selection of the substrate is limited in terms of heat resistance, and there is room for improvement in that the shape and physical properties of the substrates before fusion, specifically, the shape of voids and the like that the substrates before fusion had, the function of the functional material contained in the substrates before fusion, and the functions of the substrates before fusion due to treatment such as surface treatment, are impaired (lost). Furthermore, the method of bonding substrates together by thermal fusion also leaves room for improvement in terms of energy costs.
[0006] As a method capable of solving the problems of the conventional bonding methods, Patent Document 1 discloses a method of bonding fibrous resin in the presence of carbon dioxide in a liquid state, a gas-liquid mixture state, or a state close to liquid. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-099885 A Summary of the Invention [Problem to be solved by the invention]
[0008] Fluorine-based materials are particularly excellent in chemical resistance and non-adhesiveness, and therefore the method described in Patent Document 1 does not disclose a method for bonding substrates together using such fluorine-based materials.
[0009] One embodiment of the present invention provides an adhesive that uses a fluoroelastomer and can form an adherend having a desired shape that is less susceptible to peeling between substrates. [Means for solving the problem]
[0010] As a result of intensive research by the present inventors to solve the above problems, it has been found that the above problems can be solved by the following configuration examples. A configuration example of the present invention is as follows.
[0011] [1] An adhesive for bonding substrates in the presence of liquid, gas-liquid or near-liquid carbon dioxide, including a fluoroelastomer.
[0012] [2] The adhesive described in [1], which is an adhesive for bonding at a temperature below the melting temperature of the adhesive.
[0013] [3] The adhesive according to [1] or [2], wherein the fluoroelastomer is at least one selected from a tetrafluoroethylene-perfluorovinyl ether copolymer and a fluororubber.
[0014] [4] An adhesive comprising two or more substrates bonded together with the adhesive according to any one of [1] to [3]. [5] The adhesive according to [4], wherein at least one of the substrates is a nonwoven fabric, a woven fabric, a porous membrane or a fiber.
[0015] [6] Two or more substrates, an adhesive comprising a fluoroelastomer; Carbon dioxide in liquid, gas-liquid mixture or near-liquid state A method for producing a crimped body, comprising step 1 of crimping in the presence of
[0016] [7] The step 1 A step 1a of contacting a laminate having an adhesive layer obtained from the adhesive between substrates with liquid or gaseous carbon dioxide and applying pressure; or a step 1b of contacting a contact body obtained by contacting a substrate with the adhesive or a dried body obtained by drying the contact body with liquid or gaseous carbon dioxide and applying pressure; The method for producing a pressure-bonded body according to [6], Effect of the Invention
[0017] According to one embodiment of the present invention, a bonded body having a desired shape and which is less susceptible to peeling between substrates can be obtained by using a fluoroelastomer. Furthermore, according to one embodiment of the present invention, in the obtained bonded body, the adhesive portion has excellent chemical resistance, is less susceptible to contamination or infiltration of foreign matter through the adhesive portion, allows for a high degree of freedom in the selection of the substrate, and is capable of maintaining the shape and physical properties of the substrate prior to bonding. Furthermore, according to one embodiment of the present invention, the bonded body can be formed without applying heat from the outside, so that the bonded body can be produced at low energy cost, and the obtained bonded body also has the advantage of being easy to subject to secondary processing. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a diagram showing the peel strength of the pressure-bonded body (laminate) obtained in Example 1. [Diagram 2]The left side of Figure 2 is an SEM image of the sample surface used in Example 3, the middle side of Figure 2 is an SEM image of the surface of a comparative laminate obtained in Example 3, and the right side of Figure 2 is an SEM image of the surface of the pressed body obtained in Example 3. [Diagram 3] The left side of FIG. 3 is a photograph of the appearance of a laminate (without CO 2 ) obtained in Example 4 for comparison, and the right side of FIG. [Figure 4] The left side of FIG. 4 is a photograph showing the appearance of the pressure-bonded body obtained in Example 5, and the right side of FIG. 4 is a photograph showing the appearance of the pressure-bonded body after it was immersed in water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] <Adhesive> An adhesive according to one embodiment of the present invention (hereinafter also referred to as "the adhesive") is an adhesive used when bonding substrates in the presence of carbon dioxide in a liquid, gas-liquid mixture, or near-liquid state, and contains a fluoroelastomer.
[0020] Although it is not entirely clear why this adhesive can provide an adhesive body with the above-mentioned effects, it is believed that by adhering substrates in the presence of carbon dioxide in a liquid, gas-liquid mixture, or near-liquid state, the carbon dioxide plasticizes at least a portion of the fluoroelastomer contained in the adhesive, allowing the substrates to be bonded and joined while their shape is fixed in an interlocking state due to an anchor effect, etc.
[0021] According to one embodiment of the present invention, an adhesive can be formed without the application of external heat, and therefore the adhesive is preferably an adhesive used when bonding substrates at temperatures below the melting points of the substrates and the adhesive, more preferably an adhesive used when bonding substrates at temperatures below about 50°C, and particularly preferably an adhesive used when bonding substrates without the application of external heat.
[0022] The adhesive of the present invention may be any adhesive used when bonding substrates in the presence of carbon dioxide in a liquid, gas-liquid mixed state, or near-liquid state. In this case, carbon dioxide in a subcritical or supercritical state may be present, but it is preferable that carbon dioxide in a subcritical or supercritical state is not present, since this allows for a reduction in pressing force and allows bonding without the use of a device having a heating mechanism, etc. The above-mentioned "carbon dioxide in a state close to liquid" specifically refers to carbon dioxide in a state in which the density is 0.4 g / mL or more (about half the density of liquid carbon dioxide).
[0023] [Fluoroelastomer] The fluoroelastomer is not particularly limited, but is preferably at least one selected from tetrafluoroethylene (TFE)-perfluorovinyl ether copolymers (FFKM) and fluororubbers (FKM). The adhesive may contain two or more types of fluoroelastomers.
[0024] The FFKM is preferably a copolymer containing a constituent unit derived from TFE and a constituent unit derived from a perfluorovinyl ether, and further containing a constituent unit derived from a crosslinking site-containing monomer as required.
[0025] Suitable examples of the perfluorovinyl ether include perfluoro(alkyl vinyl ether) and perfluoro(alkoxyalkyl vinyl ether).
[0026] The perfluoro(alkyl vinyl ether) may be a compound in which the alkyl group has, for example, 1 to 10 carbon atoms. Specific examples include perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), and perfluoro(propyl vinyl ether), and is preferably perfluoro(methyl vinyl ether).
[0027] The perfluoro(alkoxyalkyl vinyl ether) may be, for example, a compound having a carbon number of 3 to 15 in the group bonded to the vinyl ether group (CF2=CFO-). CF2=CFOCF2CF(CF3)OC n F 2n+1 , CF2 = CFO(CF2)3OC n F 2n+1 , CF2 = CFOCF2CF(CF3)O(CF2O) m C n F 2n+1 , CF2 = CFO(CF2)2OC n F 2n+1 etc. In these formulas, n is, independently, for example, 1 to 5, and m is, for example, 1 to 3.
[0028] The FFKM can be provided with crosslinkability by including a structural unit derived from a crosslinking site-containing monomer. The crosslinking site means a site capable of undergoing a crosslinking reaction, and examples of such sites include a nitrile group, a halogen group (e.g., an I group, a Br group), and a perfluorophenyl group.
[0029] Examples of crosslinking site monomers having a nitrile group as a crosslinking site include nitrile group-containing perfluorovinyl ethers, and specific examples thereof include: CF2 = CFO(CF2) n OCF(CF3)CN (n is, for example, 2 to 4), CF2 = CFO(CF2) n CN (n is, for example, 2 to 12), CF2 = CFO[CF2CF(CF3)O] m (CF2) n CN (n is, for example, 2, m is, for example, 1 to 5), CF2 = CFO[CF2CF(CF3)O] m (CF2) n CN (n is, for example, 1 to 4, m is, for example, 1 to 2), CF2 = CFO[CF2CF(CF3)O] nCF2CF(CF3)CN (n is, for example, 0 to 4) etc.
[0030] Examples of crosslinking site-containing monomers having a halogen group as a crosslinking site include halogen group-containing perfluorovinyl ethers, and specific examples thereof include compounds in which the nitrile group in the specific examples of the nitrile group-containing perfluorovinyl ethers described above is replaced with a halogen group.
[0031] In FFKM, the content of constituent units derived from TFE is preferably 50.0 to 79.9 mol %, the content of constituent units derived from perfluorovinyl ether is preferably 20.0 to 46.9 mol %, and the content of constituent units derived from crosslinking site-containing monomers is preferably 0.1 to 2.0 mol %.
[0032] The FKM may be a rubber other than the FFKM, and is not particularly limited. Specific examples include vinylidene fluoride-hexafluoropropylene polymers; vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene polymers; tetrafluoroethylene-propylene polymers; vinylidene fluoride-propylene-tetrafluoroethylene polymers; ethylene-tetrafluoroethylene-perfluoromethylvinyl ether polymers; vinylidene fluoride-tetrafluoroethylene-perfluoromethylvinyl ether polymers, and vinylidene fluoride-perfluoromethylvinyl ether polymers. In order to impart crosslinkability to the FKM, the FKM may contain a constituent unit derived from a crosslinking site-containing monomer, as in the section on FFKM above.
[0033] The fluorine content of the fluoroelastomer is preferably 60% by mass or more, more preferably 62% by mass or more, particularly preferably 64% by mass or more, and is preferably 80% by mass or less, more preferably 78% by mass or less. When the fluorine content is within the above range, substrates can be easily bonded to each other, an adhered body having a desired shape in which peeling between the substrates and the like is unlikely to occur can be easily obtained, and further an adhered body having excellent chemical resistance and in which foreign matter is unlikely to be mixed in or contaminated at the adhesive portion can be easily obtained. The fluorine content can be measured or calculated by solid-state nuclear magnetic resonance (NMR) or mass spectrometry (MS spectrometry), or the like.
[0034] The content of the perfluoroelastomer relative to 100% by mass of the components other than the solvent and dispersion medium in the adhesive is preferably 90 to 100% by mass, more preferably 95 to 100% by mass, and particularly preferably 98 to 100% by mass. When the fluoroelastomer content is within the above range, substrates can be easily bonded to each other in the presence of carbon dioxide in a liquid, gas-liquid mixed state, or near-liquid state, and an adherend having a desired shape and in which peeling between the substrates is unlikely to occur can be easily obtained. Furthermore, an adherend having excellent chemical resistance and in which foreign matter is unlikely to be mixed in or contaminated at the adhesive portion can be easily obtained.
[0035] In addition to the fluoroelastomer, the adhesive may contain, as necessary, conventionally known additives such as crosslinking agents, crosslinking aids, antioxidants, antioxidants, vulcanization accelerators, processing aids (stearic acid, etc.), stabilizers, tackifiers, silane coupling agents, functional (nano)particles, plasticizers, flame retardants, waxes, and lubricants, provided that the effects of the present invention are not impaired.
[0036] Furthermore, when an adhesive obtained using this adhesive is used in a high temperature environment, there is a risk of volatilization, elution or precipitation, so it is preferable that the amount of the additives is as small as possible. Specifically, the amount is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1 part by mass or less, per 100 parts by mass of the fluoroelastomer. It is even more preferable that no additives are contained.
[0037] The adhesive may be a solid adhesive in the form of a film, fiber, line, sphere (particle), lattice, nonwoven fabric, or the like, or may be a liquid adhesive in which the fluoroelastomer or the like is dispersed or dissolved. That is, the adhesive may contain a solvent capable of dispersing or dissolving the fluoroelastomer, and in this case, it preferably contains a solvent capable of dissolving the fluoroelastomer. The concentration of the fluoroelastomer in the liquid adhesive is preferably 0.01% by mass or more, more preferably 0.5% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less.
[0038] <Base material> There are no particular limitations on the substrate to which the adhesive of the present invention can be adhered, and examples include substrates containing at least one material selected from resins, carbon materials, glass, and metals. The substrate is preferably at least one selected from nonwoven fabric, woven fabric, porous membrane, and fiber, since it is possible to easily form an adhesive body having a desired shape in which peeling between substrates is unlikely to occur.
[0039] [resin] The resin is not particularly limited, but examples thereof include fluororesins, engineering plastics, and other plastics. Among these, fluororesins and engineering plastics are preferred.
[0040] [Fluorine resin] The fluororesin is not particularly limited, and any known fluororesin can be used. The fluoroelastomer contained in the adhesive and the fluororesin constituting the substrate may be the same or different, but it is preferable that they are different, and it is more preferable that the crystallinity of the fluororesin constituting the substrate is higher than the crystallinity of the fluoroelastomer contained in the adhesive.
[0041] Specific examples of the fluorine-based resin include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer (EPE), fluoroethylene-vinyl ether copolymer (FEVE), poly(chlorotrifluoroethylene) (PCTFE), ethylene-chlorotrifluoroethylene-copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), vinylidene fluoride-hexafluoropropylene copolymer (VDF-HFP copolymer), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer (VDF-HFP-TFE copolymer), etc. Among these, PTFE and PFA are preferred.
[0042] [Engineering plastics] The engineering plastic is not particularly limited, and conventionally known engineering plastics can be used. Specific examples of the engineering plastic include polyphenylene sulfide resin (PPS), polysulfone resin, polyethersulfone resin, polyetheretherketone resin (PEEK), polyarylate resin, liquid crystal polymer, aromatic polyester resin, polyimide resin, polyamideimide resin, polyetherimide resin, aramid resin, polycarbonate resin, polyacetal resin, polyester resin such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polycyclohexylene dimethyl terephthalate (PCT), polyphenylene ether resin, polyphenylene oxide resin, polyamide resin such as nylon 6, nylon 66, and aromatic polyamide, acrylic polymer, vinyl chloride polymer, vinylidene chloride polymer, polybenzoazole resin (e.g., polybenzimidazole (PBI)), polyethylene (e.g., ultra-high molecular weight polyethylene), and polypropylene (e.g., ultra-high molecular weight polypropylene).
[0043] [Other plastics] The other plastics are not particularly limited as long as they are resins other than fluorine-based resins and engineering plastics, and conventionally known plastics can be used.Specific examples of such plastics include thermosetting resins such as polyvinyl chloride (PVC), polystyrene (PS), acrylonitrile-butadiene-styrene resin (ABS), polymethyl methacrylate resin (PMMA), phenolic resins (including straight phenolic resins and various modified phenolic resins), melamine resins, and epoxy resins.
[0044] The substrate containing the resin may contain other components such as fibers, such as carbon fibers or glass fibers, and the additives described in the adhesive section.
[0045] Examples of the form of the substrate containing the resin include fibers, porous membranes (including stretched porous membranes), nonwoven fabrics, woven fabrics, and films. In addition, when a resin-containing film is used as the substrate, it is preferable to use a film whose surface in contact with the adhesive has been roughened by a conventionally known method, in order to obtain an adhesive body in which peeling between substrates is less likely to occur, etc. In addition, since it is not easy to bond resin-containing films together, when a resin-containing film is used as the substrate, it is preferable that the substrate to be bonded to the film is a substrate through which carbon dioxide can pass, such as a fiber, a porous membrane, a nonwoven fabric, or a woven fabric.
[0046] [Carbon materials] Examples of the substrate containing a carbon material include carbon fibers, carbon nanotubes, and graphite sheets. The shape of the carbon fibers is not particularly limited, and examples of the shape include fibers, filaments, cloth, felt, mats, papers, and prepregs.
[0047] [Glass] Examples of the substrate containing glass include glass fiber, glass woven fabric, and glass nonwoven fabric. Specific examples of these include glass cloth, glass paper, glass mat, glass felt, and substrates having the above-mentioned resin on the surface thereof.
[0048] [metal] Examples of the substrate containing a metal include woven fabric, nonwoven fabric, and metal fiber (including wool-like metal). The substrate containing a metal may also be a substrate in which a support such as a fiber, a porous membrane, a nonwoven fabric, or a woven fabric is treated with a metal (e.g., a substrate in which a support is plated, or a substrate in which a metal is vapor-deposited on a support). Examples of the metal include stainless steel, aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, copper, copper alloys, gold, gold alloys, silver, silver alloys, tantalum, tantalum alloys, chromium, chromium alloys, molybdenum, molybdenum alloys, tungsten, and tungsten alloys.
[0049] As the substrate, a substrate made of a fluororesin is preferable, and a substrate made of PTFE, PFA, or the like is more preferable, because the substrate has excellent mechanical strength, heat resistance, chemical resistance, weather resistance, and electrical insulation, and an adhesive can be easily obtained in which all of the components constituting the adhesive are fluorine components. Incidentally, since fluorine components are non-adhesive and have a small coefficient of friction, it has not been possible to obtain an adhesive having a desired shape that is less susceptible to peeling between the substrates when the adhesive is made entirely of fluorine components. However, according to one embodiment of the present invention, even when using an adhesive made of such fluorine components, it is possible to easily obtain an adhesive having a desired shape that is less susceptible to peeling between the substrates.
[0050] The nonwoven fabric, woven fabric, porous membrane, fiber (tube), and film (sheet) are not particularly limited, and conventionally known nonwoven fabrics, woven fabrics, porous membranes, fibers (tubes), and films (sheets) can be used.
[0051] The substrate may be a substrate that has been subjected to a functionalization treatment such as a conventionally known surface treatment such as a hydrophilization treatment. According to one embodiment of the present invention, even if a substrate that has been subjected to such a functionalization treatment is used, it is possible to form an adhesive body without impairing the function.
[0052] The fibers constituting the nonwoven fabric or woven fabric, or the average fiber diameter of the fibers, is preferably 0.01 μm or more, more preferably 0.1 μm or more, even more preferably 0.5 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less. When the average fiber diameter is within the above range, an adhesive body having excellent mechanical strength and a desired shape that is less susceptible to fraying of fibers or peeling between substrates can be easily obtained.
[0053] The average fiber diameter is an average value calculated based on the measurement results by observing the fiber (group) to be measured with a scanning electron microscope (SEM) (magnification: 2000 times), randomly selecting 20 fibers from the obtained SEM image, and measuring the fiber diameter (long diameter) of each of these fibers.
[0054] The fiber diameter variation coefficient of the fibers constituting the nonwoven fabric or woven fabric, or of the fibers, calculated by the following formula, is preferably 0.7 or less, more preferably 0.01 or more, and more preferably 0.5 or less. When the fiber diameter variation coefficient is within the above range, the fiber diameter becomes uniform, and an adherend having a desired shape with excellent mechanical strength and with less tendency for fraying of the fibers or peeling between the substrates can be easily obtained. Coefficient of variation of fiber diameter = standard deviation / average fiber diameter (Note that the "standard deviation" refers to the standard deviation of the fiber diameters of the 20 fibers.)
[0055] The fibers constituting the nonwoven fabric or woven fabric and the fiber length of the fibers are not particularly limited, but are preferably 0.5 mm or more, more preferably 1 mm or more, and are preferably 100 mm or less, more preferably 50 mm or less.
[0056] The stretched porous membrane is not particularly limited, and may be a uniaxially stretched porous membrane or a biaxially stretched porous membrane.
[0057] The porosity of the nonwoven fabric, woven fabric or porous membrane is not particularly limited, but is, for example, 0.1 vol. % or more, preferably 30 vol. % or more, and is, for example, 95 vol. % or less, preferably 90 vol. % or less. The porosity can be calculated from the difference between the theoretical volume calculated assuming no voids based on the specific gravity of the material constituting the nonwoven fabric, woven fabric or porous membrane and the actual measured mass of the nonwoven fabric, woven fabric or porous membrane, and the actual volume calculated by measuring the dimensions of the nonwoven fabric, woven fabric or porous membrane, using the following formula. Porosity (volume%) = (1-(theoretical volume / measured volume)) x 100
[0058] The weight of the nonwoven fabric, woven fabric or porous membrane is preferably 100 g / m 2 More preferably, it is 1 g / m or less. 2 More preferably, it is 80 g / m 2 The following is the result.
[0059] The thickness of the nonwoven fabric, woven fabric, porous membrane, or film (sheet) is usually 5 μm or more, preferably 10 μm or more, and usually 1 mm or less, preferably 500 μm or less.
[0060] <Adhesive body (pressure-bonded body)> An adhesive body according to one embodiment of the present invention is formed by bonding two or more substrates with the adhesive of the present invention, and is preferably a bonded body formed by bonding two or more substrates with the adhesive of the present invention, and more preferably a bonded body obtained by the method for manufacturing a bonded body described below. The number of substrates used in the adhesive body may be two or more. In this case, two or more substrates having different materials, shapes, etc. may be used, or two or more substrates having the same material, shape, etc. may be used.
[0061] The shape and size of the adhesive body are not particularly limited and may be appropriately selected depending on the desired application. The thickness of the adhesive is not particularly limited and may be appropriately selected depending on the application, but in the case of an adhesive of a nonwoven fabric or a porous membrane, it is usually 10 μm or more, preferably 50 μm or more, and usually 30 mm or less, preferably 25 mm or less.
[0062] The adhesive can be suitably used in applications where substrates containing resins, carbon materials, glass or metals have been used, and can be particularly suitably used in the medical field, electrical equipment field, semiconductor field and the like, and specifically, can be suitably used as filters, various separators, clothing and the like.
[0063] The adhesive may contain one or more functional materials required for a desired application, such as foodstuffs, drugs (medicinal, agricultural, industrial), dyes, adsorbents, deodorants, fragrances, insect repellents, electronic device materials, enzymes, and catalysts. When the adhesive body contains such a functional material, even if the functional material has poor heat resistance, it is possible to obtain an adhesive body that makes use of the functions, properties, etc. of the functional material. For example, when a drug or the like is contained, an adhesive body with controlled sustained release or the like can be obtained.
[0064] <Manufacturing method of pressure-bonded body> A method for producing a pressure-bonded body according to one embodiment of the present invention (hereinafter also referred to as "this method") includes the steps of: an adhesive comprising a fluoroelastomer; Carbon dioxide in liquid, gas-liquid mixture or near-liquid state The method includes the step of: The substrate is preferably made of a fluororesin. In this case, the present method can be said to be a novel method for processing substrates made of a fluororesin, which is difficult to process.
[0065] According to this method, a pressure-bonded body can be produced at a low cost in a short time at a temperature of about 50°C or less without applying high heat that melts the resin constituting the substrate, and since carbon dioxide does not basically remain in the obtained pressure-bonded body, a clean pressure-bonded body with excellent safety, controllability and productivity can be easily obtained. In addition, a pressure-bonded body having a desired shape with excellent mechanical strength and less susceptible to peeling between the substrates can be easily obtained. In particular, a pressure-bonded body can be obtained while maintaining the characteristics of the substrate (e.g., function, voids in the nonwoven fabric, fiber shape). Furthermore, according to this method, when manufacturing a pressure-bonded body containing a functional material to be used according to the desired application, even if the functional material has poor heat resistance, it is possible to obtain a pressure-bonded body that makes use of the functions, properties, etc. of the functional material.
[0066] Although it is not entirely clear why this method makes it possible to obtain a bonded body having the desired shape that has excellent mechanical strength and is less likely to peel between the substrates, it is thought that this is because when pressure is applied in the presence of carbon dioxide in a liquid, gas-liquid mixture, or near-liquid state, the fluoroelastomer in the adhesive is plasticized by the carbon dioxide, and when pressure is applied in this plasticized state, the substrates can be bonded and joined while their shape is fixed in an interlocking state.
[0067] <Process 1> The step 1 is not particularly limited as long as it is a step of bonding two or more substrates under pressure in the presence of the adhesive and carbon dioxide in a liquid, gas-liquid mixture, or liquid-like state, and during this bonding, one or more functional materials required for the desired application may be used depending on the application. Examples of the functional materials include the same functional materials as those described in the adhesive section above.
[0068] In step 1, pressure may be applied by arranging an adhesive layer obtained from the adhesive in the form of a film, fiber, line, sphere (particle, dot), lattice, nonwoven fabric, or the like between the substrates, or pressure may be applied using a contact body in which the substrate and the adhesive are brought into contact, or a dried body obtained by drying the contact body. In the former case, for example, a method is used in which a film-like or fibrous adhesive layer is formed from the adhesive in advance, the adhesive layer is arranged between substrates, and pressure is applied, while in the latter case, for example, a method is used in which a substrate is immersed in the liquid adhesive, or the liquid adhesive is applied to a substrate in a desired shape (e.g., line, dot, or grid), and pressure is applied after volatilizing the solvent as necessary.
[0069] Step 1 may also be a step of forming a preliminary body by pressing one substrate and the adhesive in the presence of liquid, gas-liquid mixed, or liquid-like carbon dioxide, and then pressing the obtained preliminary body and a desired substrate to be pressed with the preliminary body, using the adhesive as necessary, in the presence of liquid, gas-liquid mixed, or liquid-like carbon dioxide.
[0070] In step 1, the substrate is compressed in the presence of carbon dioxide in a liquid state, a gas-liquid mixture state, or a state close to liquid. It is believed that when carbon dioxide in a liquid state, a gas-liquid mixture state, or a state close to liquid is brought into contact with the substrate, the carbon dioxide is impregnated into the fluoroelastomer in the adhesive, and the fluoroelastomer can be plasticized, and a compressed body can be produced without heating. In step 1, carbon dioxide in a subcritical or supercritical state may be used, but carbon dioxide in a liquid state or a gas-liquid mixed state is preferred from the viewpoints that the pressing force can be reduced and pressure bonding can be performed without using a device having a heating mechanism, etc. Also, since gaseous carbon dioxide is considered to hardly plasticize the base material or to require a considerable amount of time for plasticization, carbon dioxide in a liquid state or a gas-liquid mixed state is preferred from the viewpoints that the base material can be plasticized quickly, etc.
[0071] Specifically, the step 1 is preferably carried out by introducing liquid or gaseous carbon dioxide into the system. That is, specifically, the step 1 is preferably the following step 1a or 1b. Step 1a: A step of contacting a laminate having an adhesive layer obtained from the adhesive between substrates with liquid or gaseous carbon dioxide and applying pressure. Step 1b: A step of contacting a contact body obtained by contacting a substrate with the adhesive or a dried body obtained by drying the contact body with liquid or gaseous carbon dioxide and applying pressure.
[0072] When introducing liquid or gaseous carbon dioxide into the system, the order in which the substrate, adhesive, and carbon dioxide are introduced into the system is not particularly limited. For example, the substrate and adhesive may be introduced into a system filled with carbon dioxide, but it is preferable to introduce carbon dioxide into the system into which the substrate and adhesive have been introduced. When introducing liquid carbon dioxide, the compression step for liquefaction can be omitted compared to when introducing gaseous carbon dioxide, and therefore the compressed body can be manufactured in a short time. On the other hand, when gaseous carbon dioxide is introduced, the process is easier than when liquid carbon dioxide is introduced, and a pressure pump may be unnecessary, allowing the device to be simplified. When gaseous carbon dioxide is introduced, the introduced carbon dioxide is usually pressurized to liquefy the carbon dioxide. In this case, it is not necessary to liquefy all of the introduced carbon dioxide, and it is sufficient to liquefy at least a portion of it.
[0073] The amount of carbon dioxide introduced is not particularly limited, but when gaseous carbon dioxide is introduced and compression is performed at a temperature of 31°C (the critical temperature of carbon dioxide) or higher, carbon dioxide is introduced so that the density of carbon dioxide during compression is 0.4 g / mL or higher (about half the density of liquid carbon dioxide).
[0074] The surface pressure during pressure bonding in step 1 may be appropriately selected depending on the type and amount of the base material used, the desired shape of the pressure-bonded body, etc., but is preferably 4 MPa or more, more preferably 5 MPa or more, and there is no particular upper limit, but it is, for example, 50 MPa or less. The surface pressure is the sum of the pressure of the carbon dioxide introduced into the system and the pressing pressure.
[0075] The pressing time during pressure bonding in step 1 may be appropriately selected depending on the type and amount of the base material and adhesive used, the surface pressure and temperature during pressure bonding, etc., but is preferably 0.2 seconds or more, more preferably 1 second or more, and is preferably 15 minutes or less, more preferably 5 minutes or less.
[0076] The temperature during bonding in step 1 may be appropriately selected depending on the type and amount of base material and adhesive used, the desired shape of the bonded body, etc., but since the present method allows the desired bonded body to be obtained without applying heat, the temperature is usually 0°C or higher, preferably 20°C or higher, and usually 40°C or lower, preferably 30°C or lower, in order to more effectively exert this effect.
[0077] Step 1 may be carried out in a sealed container capable of reducing the volume, or may be carried out using an open pressing device. The sealed container may, for example, be a container having an inlet for introducing liquid or gaseous carbon dioxide into the sealed space and an outlet for carbon dioxide, and having a member such as a piston that can reduce the volume of the sealed container to press the substrate.
[0078] When an open pressing device is used, the object to be treated can be treated in a spot manner without using a large treatment container that covers the entire substrate to be treated. For example, the substrate can be sent out and pressed repeatedly in a different position, or a roller can be used instead of a piston to press the substrate, thereby continuously producing pressed bodies.
[0079] Furthermore, according to one embodiment of the present invention, unlike a pressure-bonded body obtained by thermal fusion, after carrying out step 1, a secondary processing can be carried out in which the obtained pressure-bonded body is further pressure-bonded to another substrate. EXAMPLES
[0080] Next, one embodiment of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these.
[0081] [Example 1] Nonwoven fabric made of PTFE nanofibers with an average fiber diameter of 900 nm (ZEUS Industrial Products, Inc., basis weight: 24 g / m 2 The substrate was prepared by punching a 19 mm diameter circular piece of aluminum foil (thickness: 70 μm) into a circular shape. In addition, FFKM (manufactured by 3M, product number: PFE-191TZ) was dissolved in Fluorinert (manufactured by 3M, product number: PF-5060) to prepare FFKM solutions adjusted to various concentrations (0.5 wt%, 1 wt%, 2 wt%). The obtained substrate was immersed in this FFKM solution for 10 seconds, removed from the solution, and the solvent (Fluorinert) was dried to obtain a substrate with FFKM.
[0082] Ten of the obtained substrates with FFKM were placed in a sealable container (diameter: φ20 mm, container described in JP 2018-099885 A) having a piston, a carbon dioxide inlet, and a carbon dioxide outlet, and carbon dioxide was introduced into the container at room temperature (25°C) at a vapor pressure equivalent to carbon dioxide (cylinder pressure: 6 MPa). The piston was lowered to reduce the volume inside the container (while liquefying the carbon dioxide), and a pressure of 300 N or 1000 N was applied for 10 seconds to bond the ten substrates together. After that, the carbon dioxide was instantly discharged while maintaining the pressure, and the pressure was released, and the bonded body (φ20 mm) was removed from the container.
[0083] <Peel strength test> The mechanical properties of the resulting bonded body were measured using a universal tensile testing machine (EZ-test, manufactured by Shimadzu Corporation) by tearing the bonded body in the bonding direction at a speed of 1 mm / s (applying a tensile load perpendicular to the adhesive surface) and measuring the average peel strength (N / 10 mm) of the bonded body at a displacement of 5 to 10 mm (5 to 10 seconds after tearing). The results are shown in Table 1 and Figure 1. The ● in Figure 1 indicates the results when a load of 1000 N was applied, and the ◆ in Figure 1 indicates the results when a load of 300 N was applied.
[0084] For comparison, a substrate with FFKM was obtained in the same manner as above, except that it was immersed in a 1 wt% FFKM solution, and ten of the resulting substrates with FFKM were used to prepare a laminate (without CO2) in the same manner as the preparation of the pressure-bonded body, except that carbon dioxide was not introduced, and the peel strength of the laminate was measured in the same manner as above. The results are shown in Table 1. Furthermore, for comparison, a laminate (FFKM concentration: 0 wt%) was prepared in the same manner as in the preparation of the pressure-bonded body, except that 10 substrates before immersion in the FFKM solution were used instead of the substrate with FFKM, and the peel strength of the laminate was measured in the same manner as above. The results are shown in Table 1 and Figure 1.
[0085] [Table 1]
[0086] [Example 2] Nonwoven fabric made of PTFE nanofibers with an average fiber diameter of 900 nm (ZEUS Industrial Products, Inc., basis weight: 24 g / m 2 The substrate was prepared by punching a 19 mm diameter circular piece of aluminum foil (thickness: 70 μm) into a circular shape. In addition, FKM (manufactured by Daikin Industries, Ltd., product number: G902) was dissolved in methyl ethyl ketone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to prepare FKM solutions adjusted to various concentrations (1 wt%, 2 wt%). The obtained substrate was immersed in this FKM solution for 10 seconds, removed from the solution, and then the solvent (methyl ethyl ketone) was dried to obtain a substrate with FKM.
[0087] Except for using the 10 obtained substrates with FKM, a pressure-bonded body was produced and the peel strength was measured in the same manner as in Example 1. The results are shown in Table 2. For comparison, a substrate with FKM was obtained in the same manner as above, except that it was immersed in a 1 wt% FKM solution, and 10 of the resulting substrates with FKM were used to prepare a laminate (without CO2) in the same manner as the preparation of the pressure-bonded body, except that carbon dioxide was not introduced, and the peel strength of the laminate was measured in the same manner as above. The results are shown in Table 2. Furthermore, for comparison, a laminate (FKM concentration: 0 wt%) was prepared in the same manner as in the preparation of the pressure-bonded body, except that 10 substrates before immersion in the FKM solution were used instead of the substrate with FKM, and the peel strength of the laminate was measured in the same manner as above. The results are shown in Table 2.
[0088] [Table 2]
[0089] [Example 3] Nonwoven fabric made of PTFE nanofiber (ZEUS Industrial Products, Inc., basis weight: 24 g / m 2 A solution of FFKM (PFE-191TZ) dissolved in Fluorinert (3M, product number: FC-3283) was used to form an FFKM layer (line) with a width of approximately 10 to 20 μm on a substrate (thickness: 70 μm), and the obtained laminate was punched out into a circle with a diameter of φ19 to prepare a sample.
[0090] Ten such samples were prepared, and the ten samples were stacked in the same orientation (so that the FFKM fibers were all on the top) and placed in a container. A pressure-bonded body was prepared in the same manner as in Example 1, except that a load of 1000 N was applied. For comparison, a laminate (without CO2) was produced by applying a pressure of 1000 N to 10 samples in the same manner, except that carbon dioxide was not introduced.
[0091] The surface structures of the obtained bonded body and the laminate (without CO2) on the side on which the FFKM layer was formed were observed at a magnification of 2000 times using an SEM (S-3400N, manufactured by Hitachi High-Technologies Corporation; the same device was used for the SEM below.) The results are shown in Figure 2. The left image in Figure 2 is an SEM image of the side surface on which the FFKM layer of the sample used is formed, the middle image in Figure 2 is an SEM image of the side surface on which the FFKM layer of the obtained laminate (without CO2) is formed, and the right image in Figure 2 is an SEM image of the side surface on which the FFKM layer of the obtained pressed body is formed.
[0092] In the laminate (without CO2), the FFKM fibers were simply compressed, and an FFKM layer was present on top of the nonwoven fabric made of PTFE nanofibers (middle image in Figure 2), but in the pressed body, the FFKM fibers appeared to be pushed (saturated) into the nonwoven fabric made of PTFE nanofibers (right image in Figure 2).
[0093] [Example 4] 0.5 g of PFA short fibers with an average fiber diameter of 60 μm was immersed in an FFKM solution in which FFKM (PFE-191TZ) was dissolved in Fluorinert (PF-5060) to a concentration of 1 wt%, and then removed from the solution and the solvent was dried to obtain short fibers with FFKM attached. It was confirmed by the dry weight method that approximately 0.015 g of FFKM was attached to the obtained short fibers with FFKM attached per 0.5 g of PFA short fibers.
[0094] A pressure-bonded body was produced in the same manner as in Example 1, except that approximately 0.515 g of the obtained short fibers with FFKM was used instead of the 10 sheets of substrate with FFKM, and the load was changed to 3000 N. For comparison, a laminate (without CO2) was produced in the same manner, except that no carbon dioxide was introduced, by applying a pressure of 3000 N to approximately 0.515 g of short fiber with FFKM.
[0095] Appearance photographs of the obtained pressed body and laminate (without CO2) are shown in FIG. 3. In FIG. 3, the left side is an appearance photograph of the laminate (without CO2), and the right side is an appearance photograph of the pressed body. When pressed without using CO2, a molded body of the desired shape was not obtained. On the other hand, when the pressed body was pressed using CO2, a molded body of the desired shape was obtained and the shape was maintained.
[0096] [Example 5] Instead of the nonwoven fabric made of PTFE nanofibers, a nonwoven fabric made of PTFE nanofibers with an average fiber diameter of 900 nm that had been hydrophilically treated with PVA (ZEUS Industrial Products, Inc., basis weight: 24 g / m) was used. 2A pressure-bonded body was produced in the same manner as in Example 3, except that a pressure-bonded sheet (thickness: 70 μm) was used.
[0097] A photograph of the appearance of the obtained pressure-bonded body is shown on the left side of Fig. 4. Moreover, a photograph of the appearance of the obtained pressure-bonded body after it was immersed in water and then taken out of the water is shown on the right side of Fig. 4. When immersed in water, the compressed body absorbed water due to the hydrophilic function of the PVA. The obtained compressed body maintained the hydrophilic function of the substrate before compression, and it was found that 10 substrates were compressed together.
[0098] [Example 6] An FFKM solution was prepared by dissolving FFKM (PFE-191TZ) in Fluorinert (PF-5060) to a concentration of 10 wt%, and the FFKM solution was cast into a film using a doctor blade. The solvent was then evaporated to produce an FFKM film (thickness: 50 μm). A nonwoven fabric (manufactured by ZEUS Industrial Products, Inc., basis weight: 24 g / m) consisting of the obtained FFKM film and PTFE nanofibers was prepared. 2 , thickness: 70 μm) were punched out into circles with a diameter of 19 mm. A bonded body was produced in the same manner as in Example 1, except that a FFKM film punched into a φ19 circle was sandwiched between nonwoven fabric punched into a φ19 circle instead of 10 stacked substrates with FFKM, and the load was 1000 N. A bonded body of the desired shape was produced, with part of the FFKM film pressed into the pores of the nonwoven fabric made of PTFE nanofiber.
[0099] In addition, the peel strength between the nonwoven fabrics in the obtained pressure-bonded body was measured in the same manner as in Example 1. A peel strength of 0.2 N / 10 mm or more was evaluated as ◯, and a peel strength of less than 0.2 N / 10 mm was evaluated as ×. The results are shown in Table 3.
[0100] [Comparative Example 6] Except for not introducing carbon dioxide, a laminate was produced in the same manner as in Example 6. The adhesion between the nonwoven fabrics in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0101] [Example 7] An FFKM solution was prepared by dissolving FFKM (PFE-191TZ) in Fluorinert (PF-5060) to a concentration of 10 wt%, and the FFKM solution was cast into a film. The solvent was then evaporated to produce an FFKM film (thickness: 50 μm). The obtained FFKM film and e-PTFE membrane (Advantec membrane filter T100A047A, manufactured by Advantec Toyo Co., Ltd.) were each punched out into a circle having a diameter of 19 mm. A pressure-bonded body was produced in the same manner as in Example 1, except that a FFKM film punched out into a φ19 circle was sandwiched between e-PTFE membranes punched out into a φ19 circle, and this was used instead of 10 stacked substrates with FFKM, and the load was 1000 N. A bonded body of the desired shape in which the e-PTFE membranes were bonded with sufficient strength was formed. The adhesion between the e-PTFE membranes in the obtained bonded body was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0102] [Comparative Example 7] A laminate was produced in the same manner as in Example 7, except that carbon dioxide was not introduced. The adhesion between the e-PTFE membranes in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0103] [Example 8] A pressure-bonded body was produced in the same manner as in Example 7, except that the e-PTFE membrane in Example 7 was replaced with a membrane obtained by subjecting the e-PTFE membrane to hydrophilic treatment. A bonded body of the desired shape was formed in which the hydrophilized e-PTFE membranes were bonded together with sufficient strength. It was also found that the bonded body obtained was formed while maintaining the hydrophilic function of the e-PTFE membrane before bonding. The adhesion between the hydrophilized e-PTFE membranes in the bonded body obtained was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0104] [Comparative Example 8] A laminate was produced in the same manner as in Example 8, except that carbon dioxide was not introduced. The adhesion between the hydrophilized e-PTFE membranes in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0105] [Example 9] An FFKM solution was prepared by dissolving FFKM (PFE-191TZ) in Fluorinert (PF-5060) to a concentration of 10 wt%, and the FFKM solution was cast into a film. The solvent was then evaporated and the film was punched out into a circle with a diameter of 19 mm to produce an FFKM film (thickness: 50 μm). Nonwoven fabric made of PTFE nanofibers with an average fiber diameter of 900 nm (ZEUS Industrial Products, Inc., basis weight: 24 g / m 2 A nonwoven fabric substrate was prepared by punching a 19 mm diameter circular piece from a 30-mm-thick PET film (70 μm thick). An e-PTFE membrane substrate was also prepared by punching a 19 mm diameter circular piece from an e-PTFE membrane (Advantec membrane filter T100A047A).
[0106] A circular FFKM film punched out with a diameter of 19 mm was sandwiched between the obtained nonwoven fabric substrate and the e-PTFE membrane substrate, and this was used instead of 10 substrates with FFKM stacked together. A pressure-bonded body was produced in the same manner as in Example 1, except that the load was 1000 N. A bonded body of the desired shape was formed in which the nonwoven fabric substrate and the e-PTFE membrane substrate were bonded with sufficient strength. The adhesion between the nonwoven fabric substrate and the e-PTFE membrane substrate in the obtained bonded body was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0107] [Comparative Example 9] A laminate was produced in the same manner as in Example 9, except that carbon dioxide was not introduced. The adhesion between the nonwoven fabric substrate and the e-PTFE membrane substrate in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0108] [Example 10] An FFKM solution was prepared by dissolving FFKM (PFE-191TZ) in Fluorinert (PF-5060) to a concentration of 10 wt%, and this FFKM solution was cast using a doctor blade onto the roughened surface of a PTFE film [a film with a roughened surface of Valflon #7900 (thickness: 50 μm) made by Valqua Corporation] and the solvent was volatilized to produce a laminated film (thickness: 65 μm). This laminated film and a nonwoven fabric made of PTFE nanofiber (ZEUS Industrial Products, Inc., basis weight: 24 g / m 2 A laminate was produced in the same manner as in Example 1, except that a nonwoven fabric (10 sheets of FFKM attached base material, thickness: 70 μm) was punched out into a circle with a diameter of 19 mm, and then the nonwoven fabric and the FFKM were overlapped so that they were in contact with each other. This was used instead of the 10 sheets of base material with FFKM overlapped, and the load was 300 N. A bonded body having a desired shape in which the PTFE film and the nonwoven fabric were bonded with sufficient strength was formed. The adhesion between the PTFE film and the nonwoven fabric in the obtained bonded body was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0109] [Comparative Example 10] A laminate was produced in the same manner as in Example 10, except that carbon dioxide was not introduced. The adhesion between the PTFE film and the nonwoven fabric in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 3.
[0110] [Table 3]
[0111] [Example 11] A pressure-bonded body was produced in the same manner as in Example 6, except that a nonwoven fabric made of a liquid crystal polymer (Veculus MBBK11F, manufactured by Kuraray Co., Ltd.) was used instead of the nonwoven fabric made of PTFE nanofiber in Example 6, and the load was set to 300 N. In addition, the adhesion between the nonwoven fabrics in the obtained pressure-bonded body was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0112] [Comparative Example 11] Except for not introducing carbon dioxide, a laminate was produced in the same manner as in Example 11. The adhesion between the nonwoven fabrics in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0113] [Example 12] A bonded body was produced in the same manner as in Example 6, except that a glass fiber cloth (ATG26100-1, manufactured by Sakai Sangyo Co., Ltd.) was used instead of the nonwoven fabric made of PTFE nanofiber in Example 6, and the load was set to 300 N. In addition, the adhesion between the cloths in the obtained bonded body was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0114] [Comparative Example 12] Except for not introducing carbon dioxide, a laminate was produced in the same manner as in Example 12. The adhesiveness between the cloths in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0115] [Example 13] A bonded body was produced in the same manner as in Example 6, except that a carbon fiber cloth (EC-CC1-060, manufactured by Electro Chem) was used instead of the nonwoven fabric made of PTFE nanofiber in Example 6, and the load was set to 300 N. In addition, the adhesiveness between the cloths in the obtained bonded body was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0116] [Comparative Example 13] A laminate was produced in the same manner as in Example 13, except that carbon dioxide was not introduced. The adhesiveness between the cloths in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0117] [Example 14] A bonded body was produced in the same manner as in Example 6, except that a stainless steel fiber cloth (SUS304 mesh 400-023, manufactured by NBC Meshtec Co., Ltd.) was used instead of the nonwoven fabric made of PTFE nanofiber, and the load was set to 300 N. The adhesiveness between the cloths in the obtained bonded body was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0118] [Comparative Example 14] A laminate was produced in the same manner as in Example 14, except that carbon dioxide was not introduced. The adhesiveness between the cloths in the obtained laminate was evaluated in the same manner as in Example 6. The results are shown in Table 4.
[0119] [Table 4]
Claims
1. 1. An adhesive comprising a fluoroelastomer, An adhesive for bonding substrates (excluding carbon materials) in the presence of carbon dioxide in liquid or gas-liquid mixed state and in the absence of organic solvents.
2. The adhesive of claim 1 , which is an adhesive for bonding at a temperature below the temperature at which the adhesive melts.
3. 3. The adhesive according to claim 1, wherein the fluoroelastomer is at least one member selected from the group consisting of tetrafluoroethylene-perfluorovinyl ether copolymers and fluororubbers.
4. The adhesive described in any one of claims 1 to 3, wherein the adhesive is a solid adhesive selected from a film-like, fibrous, line-like, particle-like, lattice-like or nonwoven fabric-like adhesive.
5. The adhesive described in any one of claims 1 to 4, wherein the substrate is at least one selected from a nonwoven fabric, a woven fabric, a porous membrane, and a fiber.
6. A bonded structure in which two or more substrates are bonded with the adhesive according to any one of claims 1 to 5.
7. The adhesive of claim 6 , wherein at least one of the substrates is a nonwoven fabric, a woven fabric, a porous membrane, or a fiber.
8. Two or more substrates, an adhesive comprising a fluoroelastomer; Carbon dioxide in liquid or gas-liquid state A method for producing a pressure-bonded body, comprising step 1 of performing pressure bonding in the presence of and in the absence of an organic solvent, and not including a step of kneading the base material and the adhesive.
9. The step 1 comprises: Step 1a of contacting a laminate having an adhesive layer obtained from the adhesive between substrates with liquid or gaseous carbon dioxide and applying pressure; or A step 1b of contacting a contact body obtained by contacting a substrate with the adhesive or a dried body obtained by drying the contact body with liquid or gaseous carbon dioxide and applying pressure. The method for producing a pressure-bonded body according to claim 8,
Citation Information
Patent Citations
Method for gas fusion of heat fusible member together and gas fusion apparatus used for it
JP1998044244A
Preparation of pressure-sensitive adhesive, pressure- sensitive adhesive composition and method for forming stable dispersion of pressure-sensitive adhesive polymer
JP2000129241A
Plastic joining method, plastic joining apparatus, and plastic product joined by using the method
JP2006116803A
Optical element and method for manufacturing same
JP2007139971A
Manufacturing method of composite particles
JP2008055261A